2013
DOI: 10.1021/jm3014376
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Evaluation of Vinblastine Analogues Containing Systematic Deep-Seated Modifications in the Vindoline Subunit Ring System: Core Redesign

Abstract: The total synthesis of a systematic series of vinblastine analogues that contain deep-seated structural modifications to the core ring system of the lower vindoline subunit is described. Complementary to the vindoline 6,5 DE ring system, compounds with 5,5, 6,6 and the reversed 5,6 membered DE ring systems were prepared. Both the natural cis and unnatural trans 6,6-membered ring systems proved accessible, with the latter representing a surprisingly effective class for analogue design. Following Fe(III)-promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 79 publications
(64 reference statements)
0
50
0
Order By: Relevance
“…83,84 Combined with the use of a single-step Fe(III)-promoted coupling of catharanthine with vindoline and a newly developed in situ Fe(III)/NaBH4-promoted hydrogen atom transfer free radical C20′ oxidation, 78,79,85,86 the approach provides vinblastine and its analogs in 8–13 steps. This was used to provide vinblastine analogs not previously accessible by semisynthetic modification of the natural products themselves that contain changes within either the lower vindoline-derived 8796 or upper catharanthine-derived subunits 97102 with the late stage divergent 103 introduction of new functionality. In addition to the examination of C10′ substituents, 64 we have prepared more than 400 analogs of vinblastine, defining the role of individual structural features and substituents.…”
Section: Introductionmentioning
confidence: 99%
“…83,84 Combined with the use of a single-step Fe(III)-promoted coupling of catharanthine with vindoline and a newly developed in situ Fe(III)/NaBH4-promoted hydrogen atom transfer free radical C20′ oxidation, 78,79,85,86 the approach provides vinblastine and its analogs in 8–13 steps. This was used to provide vinblastine analogs not previously accessible by semisynthetic modification of the natural products themselves that contain changes within either the lower vindoline-derived 8796 or upper catharanthine-derived subunits 97102 with the late stage divergent 103 introduction of new functionality. In addition to the examination of C10′ substituents, 64 we have prepared more than 400 analogs of vinblastine, defining the role of individual structural features and substituents.…”
Section: Introductionmentioning
confidence: 99%
“…2830 As a result of these developments, we have prepared several series of key analogs, systematically exploring and defining the impact individual structural features and substituents have on tubulin binding affinity and cancer cell growth inhibition. 10,19 Complementary to the studies detailed herein, we have systematically probed the impact and role of the vindoline C4 acetate, 31,32 C5 ethyl substituent, 33 C6–C7 double bond, 3436 and the vindoline core structure itself, 36 and have systematically explored the upper catharanthine-derived subunit C20’ ethyl substituent, 37,38 C16’ methyl ester, 39 and added C10’ or C12’ indole substitutions. 40 In addition and in preceding studies, we have shown that replacement of the C20'-OH with 20’ ureas was possible, 41 that substantial 42 and even remarkable 43 potency enhancements were obtainable with such 20’ ureas, and that some exhibited further improvements in activity against vinblastine-resistant cancer cell lines.…”
Section: Introductionmentioning
confidence: 91%
“…64 The 5,5-vindoline subunit analogue was accessed through an intermediate previously enlisted in the asymmetric synthesis of vindoline, 56 where a remarkably facile thermal deformylation reaction of 10 generated 11 directly (50%). 64 Presumably this unusual reaction occurs by reversible iminium ion formation followed by loss of formaldehyde to generate a stabilized singlet carbene that undergoes an insertion of the proximal C3 alcohol for reclosure of the N,O -ketal, affording the 5,5-D,E ring analogue of vindoline (Figure 11b). Increasing the length of the dipolarophile tether by one carbon and varying the length of the dienophile tether provided cycloadducts bearing the corresponding 6,5- and 6,6-DE ring system analogues.…”
Section: Applications In the Total Synthesis Of Natural Productsmentioning
confidence: 99%
“…Most interesting in this probe was that it was the analogues that bore the greatest departure from the natural products ( 12 and 13 ) that exhibited the best activity, matching that of the comparison natural products. 64 Unlike modifications to peripheral substituents, such core redesign is rarely explored in complex natural products, and was possible only because of the power of the oxadiazole cycloaddition cascade.…”
Section: Applications In the Total Synthesis Of Natural Productsmentioning
confidence: 99%